Determination of Maximum Unsupported Span and Stand Up Time Value using Q-System Method (Case Study: Pongkor Area, Nanggung Subdistrict, Bogor District, West Java Province) - Alisah, Alisah; Sophian, Irvan; Zakaria, Zufialdy; Pratama, Ryan; Firmansyah, Yusi (Faculty of Geological Engineering, Universitas Padjadjaran, 2018)
Epithermal deposit might be a potential economic mining source. One kind of this deposit is the low-sulphidation epithermal with the quartz vein which can be found in the study area. However, the high intensity number of the alteration process will affect the rock mass quality in the area of interest which also will influence the safety of underground mining process, ecspecially while the tunnel reinforcement is being set. Therefore, maximum unsupported span and stand up time value need to be determined.Study area is Nanggung Subdistrict, Bogor District, West Java Province. This study is conducted at some fronts in Ciguha tunnel, using the Q system methode. After the rock mass has been classified, the maximum unsupported span and stand up time value can be calculated.The result shows that maximum unsupported span value has a variety number from 8 hours to 1 year extend. At the other side, stand up time value also has a variety number from 1 to 4 meters span. Both shows a value depends on their own rock mass quality. Keyword: Q- System, Stand up time, Maximum unsupported span